Comparative study on the performance of capacitive mixing under different operational modes. (November 2022) - Zou, Zhi; Liu, Longcheng; Meng, Shuo; Bian, Xiaolei
Abstract: Capacitive mixing (CapMix) is a renewable method of extracting energy from the salinity difference between seawater and freshwater. In this study, we systematically investigate the system behavior and performance of the CapMix system under four operational modes namely, capacitive energy extraction based on double layer expansion (CDLE), capacitive energy extraction based on the Donnan potential (CDP), and CDP with additional charging of constant voltage (CDP-CV) and constant current (CDP-CC). The results indicate that the application of additional charging in the CDP technique can break the limits of the Donnan potential and significantly improve the system's performance. Accordingly, in terms of energy production and average power density, CDP-CC and CDP-CV are the two superior operational modes, followed by CDP and CDLE. In addition, our results reveal that CDP-CC is determined by the accumulated charge and applied current. CDLE is dependent on the applied voltage, while CDP-CV is not sensitive to the applied voltage. Increasing the external load can considerably increase the energy production of both CDLE and CDP. In summary, the findings in this study provide practical information for the optimization and application of CapMix technologies. Graphical abstract: